2017
DOI: 10.3389/fpls.2017.00135
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters a Lot: Drought-Affected Italian Oaks Are Smaller and Show Lower Growth Prior to Tree Death

Abstract: Hydraulic theory suggests that tall trees are at greater risk of drought-triggered death caused by hydraulic failure than small trees. In addition the drop in growth, observed in several tree species prior to death, is often interpreted as an early-warning signal of impending death. We test these hypotheses by comparing size, growth, and wood-anatomy patterns of living and now-dead trees in two Italian oak forests showing recent mortality episodes. The mortality probability of trees is modeled as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 95 publications
(127 reference statements)
12
64
0
4
Order By: Relevance
“…We found that dead oaks were characterized as smaller than surviving oaks, as previously reported [17,50]. This suggests that a smaller size predisposes to drought-induced dieback and death through a lower capacity to buffer the negative effects of soil water deficit by increasing hydraulic capacitance [79].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We found that dead oaks were characterized as smaller than surviving oaks, as previously reported [17,50]. This suggests that a smaller size predisposes to drought-induced dieback and death through a lower capacity to buffer the negative effects of soil water deficit by increasing hydraulic capacitance [79].…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, we have shown that taller oaks were more prone to survive after drought than smaller oaks [50]. We applied Firth's bias-Reduced penalized-likelihood logistic regression [51,52].…”
Section: Comparing Living and Recently Dead Trees: Features Mortalitmentioning
confidence: 99%
“…Forest structure mediates the effect of drought on oak forest dynamics at several scales (Clark et al, 2016;Colangelo et al, 2017b). Indeed, recruitment patterns and mortality in several oak species seem to be related to canopy closure (Gómez-Aparicio et al, 2008).…”
Section: Competition Increases Persian Oak Decline and Mortalitymentioning
confidence: 99%
“…Notwithstanding, such suppressed and presumably older stems, growing as coppices, might be particularly vulnerable to decline (Hamzehpour et al, 2011). Specifically, these trees subjected to higher competition show lower radial growth and they are more prone to die following extreme drought events (Franklin et al, 1987;Das et al, 2008Das et al, , 2011Colangelo et al, 2017b). Greater mortality in coppice oaks could be related with the abandonment of stems harvest at earlier age, or with the undone reduction of the number of stems of each coppice, both management practices that could reduce stand-level decline and mortality (Di Filippo et al, 2010).…”
Section: Competition Increases Persian Oak Decline and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation